Use of social media in health care by patients and health care professionals: motives & barriers in Thailand - SRIMARUT, T.; TECHASATIAN, K. (Utopía y Praxis Latinoamericana, 2019)
ABSTRACT The purpose of this study was to examine the motives and barriers in the use of social media in healthcare for patients and healthcare professionals. It was found that patients and healthcare professional users constituted on Facebook (62.9%), on Twitter (49.4%) on YouTube (13.4%). The use of Facebook among patients was superior (89%) because it is now becoming a household social networking site. LinkedIn among healthcare professionals was superior (95%) because it is becoming an extended network of colleagues. The results suggested a strong variance in patients and health care physicians motives for the use of social media. RESUMEN El propósito de este estudio fue examinar los motivos y las barreras en el uso de las redes sociales en la atención médica para pacientes y profesionales de la salud. Se encontró que los pacientes y usuarios profesionales de la salud se constituyeron en Facebook (62.9%), en Twitter (49.4%) en YouTube (13.4%). El uso de Facebook entre los pacientes fue mayor (89%) porque ahora se está convirtiendo en un sitio de redes sociales para el hogar. LinkedIn entre los profesionales de la salud fue el sitio más grande (95%) debido a que es una red extendida de colegas. Los resultados sugieren una fuerte variación en los motivos de los pacientes y los médicos para el uso de las redes sociales.